Achilles tendon biomechanics in psoriatic arthritis patients with ultrasound proven enthesitis. (August 2013) - Woodburn, J; Hyslop, E; Barn, R; McInnes, IB; Turner, DE
<x xml:space="preserve">Abstract</x> Objective: To investigate Achilles tendon (AT) biomechanics in psoriatic arthritis (PsA) patients with ultrasound confirmed features of enthesitis. Method: PsA patients and healthy control subjects underwent three-dimensional (3D) gait analysis to measure walking speed, rotational joint motion and the moments, power, and AT force at the ankle–subtalar joint complex. The Glasgow Ultrasound Enthesitis Scoring System (GUESS) was used to score the presence of enthesophytes, erosions, retrocalcaneal bursitis, and tendon thickening. Power Doppler ultrasound signal (PDUS) was used to detect active disease. Peripheral joint arthritis, acute-phase reactants, global health, disability, and foot impairments were recorded. A core set of biomechanical variables that influence the insertion of the AT and indirect estimates of tendon loading were compared between PsA patients and control subjects with and without enthesitis. Results: Forty-two PsA patients with a mean disease duration of 10.6 (SD 9.4) years and 29 control subjects were studied. Seventeen (40%) PsA patients had clinically detectable AT entheseal pain. Twenty-eight (67%) PsA patients and nine (31%) control subjects had one or more GUESS enthesitis features, predominantly enthesophytes. PsA patients with enthesitis walked significantly more slowly than control subjects (p = 0.019) and generated lower peak ankle joint moments (p = 0.006), power (p = 0.001), and AT force (p = 0.003). Ankle–subtalar joint complex motion was comparable and no between-group differences were found for peak dorsiflexion (p = 0.59), eversion (p = 0.05), and internal rotation (p = 0.19). Conclusions: In this group of PsA patients, the AT insertional angle was not influenced by ankle–subtalar joint motion in those with and without enthesitis. Moreover, the PsA patients with enthesitis had significantly lower AT loading.